OPTIONS FOR USE OF APPROPRIATE ANTICOAGULANT THERAPY IN PATIENTS WITH THERMAL INJURY WITH A HIGH RISK OF THROMBOEMBOLIC COMPLICATIONS DEVELOPMENT ASSOCIATED WITH RECURRENT INTESTINAL BLEEDING - V. S. Borisov; S. V. Smirnov; E. V. Klychnikova; L. F. Tveritneva; E. I. Sergeyeva; N. A. Nabatchikova (Неотложная медицинская помощь)
ABSTRACT. Patients with major thermal injury require anticoagulant therapy during almost the whole period of the burn disease, forcing the physician to balance constantly between the risk of possible bleeding associated with surgical treatment and the risk of thrombosis development in patients demonstrating a number of factors predisposing to the development of VTС. We report a clinical case of appropriate anticoagulant therapy using the new oral anticoagulants in a patient with a high risk of VTС development and recurrent bleeding from the tumor of the ascending colon.